Pengaruh Kualitas Pelayanan dan Penetapan Harga terhadap Kepuasan Konsumen pada Objek Wisata Slanik Waterpark di Lampung Selatan - Suhartina; Shoheh, Rusli (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2023)
Research was conducted to determine and explain the influence of service quality and pricing on consumer satisfaction at the Slanik Waterpark tourist attraction in South Lampung. This research was conducted on visitors to the Slanik Waterpark tourist attraction with a sample size of 115 respondents and used the Slovin formula calculation. This research method is quantitative with an associative and causal approach using data collection techniques in the form of questionnaires and there are two independent variables, namely service quality (X1) and pricing (X2), with the dependent variable namely consumer satisfaction (Y). The results of this study showed that the respondents were dominated by the 21-30 year age range, 59 people or 51%, 60 people or 52% female, and 47 students or 41% students. H1 was accepted with a tcount value of 6.398 and a sig level of 0.000, H2 was accepted with a tcount value of 6.471 and a sig level of 0.000 and H3 was accepted with a fcount value of 185.595 and a sig level of 0.000. Service quality and pricing have a significant partial or simultaneous effect on consumer satisfaction at the Slanik Waterpark tourist attraction with an r-square value of 76.8%. Meanwhile, the remaining 23.2% is influenced by other variables. Keywords: consumer satisfaction, service quality, pricing